A single dose of doxycycline after an ixodes ricinus tick bite to prevent Lyme borreliosis: An open-label randomized controlled trial. Issue 1 (January 2021) - Harms, M.G.; Hofhuis, A.; Sprong, H.; Bennema, S.C.; Ferreira, J.A.; Fonville, M.; Docters van Leeuwen, A.; Assendelft, W.J.J.; Van Weert, H.C.P.M.; Van Pelt, W.; Van den Wijngaard, C.C.
Highlights: Single dose doxycycline prevents Lyme borreliosis after an I. ricinus tick bite. Prophylaxis efficacy between Europe and North America is similar, while ticks are not. Online inclusion enables large tick bite studies. Prophylaxis efficacy is greatly increased dependent on tick characteristics. Abstract: Objectives: A single dose of doxycycline after a tick bite can prevent the development of Lyme borreliosis in North America, but extrapolation to Europe is hampered by differences in Borrelia burgdorferi sensu lato genospecies and tick species. We assessed the efficacy of prophylaxis after a tick bite in Europe. Methods: We conducted an open-label randomized controlled trial, administering a single dose of 200 mg doxycycline within 72 h after removing an attached tick from the skin, compared to no treatment. Potential participants ≥ 8 years of age who reported a recent tick bite online were invited for the study. After informed consent, they were randomly assigned to either the prophylaxis or the no-treatment group. Participants in the prophylaxis group were asked to visit their general practitioner to administer the antibiotics. All participants were followed up by online questionnaires. Our primary outcome was the development of physician-confirmed Lyme borreliosis in a modified-intention-to-treat analysis. This study is registered in the Netherlands Trial Register (NTR3953) and is closed. Results: Between April 11, 2013, and June 10, 2015, 3538 potential participants were randomized, of whom 1689 were included in the modified-intention-to-treat analysis. 10 cases of Lyme borreliosis were reported out of 1041 participants (0.96%) in the prophylaxis group, and 19 cases out of 648 no-treatment participants (2.9%), resulting in a relative risk reduction of 67% (95% CI 31 - 84%), and a number-needed-to-treat of 51 (95% CI 29 - 180). No serious adverse events were reported. Conclusions: This primary care-based trial provides evidence that a single dose of doxycycline can prevent the development of Lyme borreliosis after an Ixodes ricinus tick bite.